Result Analysis for Particle Swarm Optimization and Genetic Algorithm for Load Flow Study - Ghosh, Poulami; Gopal Mukherjee, Anand; Kumar Singh, Siddharth; Prasad Dubey, Hari (International Journal of Computer Sciences and Engineering, 2025)
This paper presents a comparative study between Particle Swarm optimization and Genetic Algorithm based methodology for solving load flow in electrical power systems. Load flow study provides the system status in steady-state and is required by several functions performed in power system control rooms.